Evaluasi dan Perbaikan Desain Interaksi Edunex dengan Pendekatan User-Centered Design - Alya Mizani; Fetty Fitriyanti Lubis (Jurnal Sistem Cerdas, 2022)
Edunex is the Learning Management System used in Institut Teknologi Bandung to support online and hybrid learning and teaching activities. However, there are still some improvements that could be implemented in order to further meet the users’ needs. To do so, the user-centered design approach is used. The development prioritizes implementing fixes in Homepage, My Courses, Exams, and Presences because those pages have high values towards users and high feasibility to fix. Besides that, based on the questionnaire that had been shared, there are needs for new features, such as Reminder and Tutorial that need to be implemented. The outcome of this project is a high-fidelity prototype of a website for desktop screens that fulfills usability and user experience goals effective to use, efficient to use, easy to learn, and helpful. The usability and user experience goals were measured using Completion Rate for effective to use, Single Ease Question (SEQ) for easy to learn, System Usability Scale (SUS) for efficient to use, and Intrinsic Motivation Inventory (IMI) with value/usefulness subscale for helpful. After conducting the evaluation by usability testing, Completion Rate value of 100%, SEQ of 6,9 out of 7, SUS value of 90 out of 100, and IMI value/usefulness value of 6,7 per 7 are achieved. Based on those values, it could be concluded that the prototype designed has fulfilled the usability and user experience goals.